Analysis of cashback promotion in the fintech industry among user interaction - Firda Awalul Nurjanah; Rita Ambarwati; Herlinda Maya Kumala Sari (Universitas Ahmad Dahlan, 2023)
The development of technology and the ease of use of online-based services have given rise to various forms of breakthroughs in the field of new technology in society. This study aims to determine whether cashback promotions can shape customer engagement in the social customer relationship management network on Gopay, OVO, and LinkAja on Twitter. The data used in this study is secondary data, which is tweets containing interactions between Twitter users regarding three fintechs in Indonesia, namely Gopay, OVO, and LinkAja. The total tweet data in all e-wallets is 3,603 from 2018-2022. Data analysis used by researchers uses the social network analysis method by calculating and comparing the network properties of cashback promotional content for the three research objects from 2018-2020 and 2020-2022. The results show that cashback promotional content on the Gopay e-wallet in 2020-2022 has better network property performance to form more optimal customer engagement.